Answer:
b. When you divide both sides by 2x = 6x it could lead us to think that there is no solution while, in fact, the solution is x = 0.
Step-by-step explanation:
The solution is correct up to the step 2x = 6x
2x = 6x
Subtract 2x from both sides.
0 = 4x
Divide both sides by 4.
x = 0
You cannot divide both sides by x since x could be zero, and in fact, it is.
Answer: b. When you divide both sides by 2x = 6x it could lead us to think that there is no solution while, in fact, the solution is x = 0.
Answer:
The value of k is -9
Step-by-step explanation:
Subsitute
g(x)=h(x)+k
![(x^2-6)=(x^2+3)+k](https://tex.z-dn.net/?f=%28x%5E2-6%29%3D%28x%5E2%2B3%29%2Bk)
![x^2-6=x^2+3+k](https://tex.z-dn.net/?f=x%5E2-6%3Dx%5E2%2B3%2Bk)
subtract
from both sides (or add
to both sides)
![-9=k](https://tex.z-dn.net/?f=-9%3Dk)
![k=-9](https://tex.z-dn.net/?f=k%3D-9)
Answer: D. all real numbers less than or equal to –3
Pi radians is 180 degrees.
A
1) 180/3=60
2) 270
3) 45
4) 3240
B
1) 100/180=5/9
3) 30/180=3/18
5) 1/180
C
1) (pi) cm
2) 2pi
For this case we must find the product of the following expression:
![\sqrt [3] {5} * \sqrt {2}](https://tex.z-dn.net/?f=%5Csqrt%20%5B3%5D%20%7B5%7D%20%2A%20%5Csqrt%20%7B2%7D)
By definition of properties of powers and roots we have:
![\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}](https://tex.z-dn.net/?f=%5Csqrt%20%5Bn%5D%20%7Ba%20%5E%20m%7D%20%3D%20a%20%5E%20%7B%5Cfrac%20%7Bm%7D%20%7Bn%7D%7D)
We rewrite the expression using the lowest common index of 6, then:
![5 ^ {\frac {1} {3}} * 2 ^ {\frac {1} {2}} =](https://tex.z-dn.net/?f=5%20%5E%20%7B%5Cfrac%20%7B1%7D%20%7B3%7D%7D%20%2A%202%20%5E%20%7B%5Cfrac%20%7B1%7D%20%7B2%7D%7D%20%3D)
We rewrite the terms in an equivalent way:
![5 ^ {\frac {2} {6}} * 2 ^ {\frac {3} {6}} =](https://tex.z-dn.net/?f=5%20%5E%20%7B%5Cfrac%20%7B2%7D%20%7B6%7D%7D%20%2A%202%20%5E%20%7B%5Cfrac%20%7B3%7D%20%7B6%7D%7D%20%3D)
We rewrite the expression using the property mentioned:
![\sqrt [6] {5 ^ 2} * \sqrt [6] {2 ^ 3} =](https://tex.z-dn.net/?f=%5Csqrt%20%5B6%5D%20%7B5%20%5E%202%7D%20%2A%20%5Csqrt%20%5B6%5D%20%7B2%20%5E%203%7D%20%3D)
We combine using the product rule for radicals:
![\sqrt [n] {a} * \sqrt [n] {b} = \sqrt [n] {ab}](https://tex.z-dn.net/?f=%5Csqrt%20%5Bn%5D%20%7Ba%7D%20%2A%20%5Csqrt%20%5Bn%5D%20%7Bb%7D%20%3D%20%5Csqrt%20%5Bn%5D%20%7Bab%7D)
So:
![\sqrt [6] {5 ^ 2 * 2 ^ 3} =\\\sqrt [6] {25 * 8} =\\\sqrt[6]{200}](https://tex.z-dn.net/?f=%5Csqrt%20%5B6%5D%20%7B5%20%5E%202%20%2A%202%20%5E%203%7D%20%3D%5C%5C%5Csqrt%20%5B6%5D%20%7B25%20%2A%208%7D%20%3D%5C%5C%5Csqrt%5B6%5D%7B200%7D)
ANswer:
Option b